Replication stress in hematopoietic stem cells in mouse and man - Flach, Johanna; Milyavsky, Michael (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 2018)
Life-long blood regeneration relies on a rare population of self-renewing hematopoietic stem cells (HSCs). These cells’ nearly unlimited self-renewal potential and lifetime persistence in the body signifies the need for tight control of their genome integrity. Their quiescent state, tightly linked with low metabolic activity, is one of the main strategies employed by HSCs to preserve an intact genome. On the other hand, HSCs need to be able to quickly respond to increased blood demands and rapidly increase their cellular output in order to fight infection-associated inflammation or extensive blood loss. This increase in proliferation rate, however, comes at the price of exposing HSCs to DNA damage inevitably associated with the process of DNA replication. Any interference with normal replication fork progression leads to a specialized molecular response termed replication stress (RS). Importantly, increased levels of RS are a hallmark feature of aged HSCs, where an accumulating body of evidence points to causative relationships between RS and the aging-associated impairment of the blood system’s functional capacity. In this review, we present an overview of RS in HSCs focusing on its causes and consequences for the blood system of mice and men.